Cage Metal Complexes: Synthesis, X‐ray Structure, and Spectral and Redox Behavior of the First Hybrid Iron(II) Clathrochelatoscorpionate and Its Pyrazoloxime‐Armed Macrocyclic Intermediate (Eur. J. Inorg. Chem. 12/2013). Issue 12 (12th April 2013) - Varzatskii, Oleg A.; Kats (Menkach), Svitlana V.; Penkova, Larysa V.; Volkov, Sergey V.; Dolganov, Alexander V.; Vologzhanina, Anna V.; Bubnov, Yurii N.; Voloshin, Yan Z.
Abstract : The cover picture shows the X‐ray structure of the first clathrochelatoscorpionate with a macrobicyclic encapsulating ligand that forms a "shell" round the caged iron(II) ion; this "shell" almost completely isolates it from external factors. One of the chelate ribbed fragments of this hybrid molecule contains a pyrazolate donor group that usually gives the so‐called "scorpionates" – the tripodal tris(pyrazolate) ligands. The structural similarity of these two types of intensively studied metal complexes (i.e., the clathrochelates and the scorpionates) was used to design hybrid complexes that are described in the Short Communication by O. A. Varzatskii, Y. Z. Voloshin et al. on p. 1987 ff.